Advances in multidisciplinary analysis and optimization : proceedings of the 2nd National Conference on Multidisciplinary Analysis and Optimization /: proceedings of the 2nd National Conference on Multidisciplinary Analysis and Optimization. (2020) - Unknown
No abstract available